Secondary battery, preparation method thereof and electric equipment
By designing a secondary battery with an optimized SEI structure in a lithium-ion battery, the mass ratio regulation of free and non-free electrolytes is used to solve the problem of low energy efficiency of lithium-ion batteries, and low impedance, high stability and high energy efficiency battery performance is achieved.
Patent Information
- Application Number
- CN202411803124.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing lithium-ion batteries have low energy efficiency during circulation, mainly due to the internal resistance of the battery and connectors that consume electricity, SEI growth and irreversible lithium-ion loss lead to energy loss, making it difficult to further improve energy efficiency through existing methods.
A secondary battery is designed, and its electrolyte includes free and non-free electrolytes. By adjusting the mass ratio of sulfonate and sulfate compounds, the SEI structure is optimized, so as to achieve the purpose of low impedance, high stability and SEI regulation as required.
By optimizing the SEI structure, the cycle energy efficiency of lithium-ion batteries is improved, low-impedance and high-stability battery performance is achieved, and the economic benefits of the battery are enhanced.
Smart Images

Figure SMS_5 
Figure SMS_8 
Figure SMS_9
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and a preparation method thereof, and electrical equipment. Background Art
[0002] As the installed capacity of renewable energy increases, the power system needs high flexibility to ensure the reliability and continuity of energy supply. Lithium-ion batteries with lithium iron phosphate (LiFePO4) positive electrode and graphite negative electrode system have the characteristics of low cost, high safety and long life, and have been applied in the field of electrochemical energy storage power stations.
[0003] The ratio of the discharge energy to the charge energy of the battery during the cycle is the round-trip energy efficiency (RTE). During the charge and discharge process, the internal resistance of the battery and the connector will consume some of the electrical energy. At the same time, SEI (solid electrolyte interface) growth and irreversible lithium deposition loss will also lead to energy loss. In the economic benefit calculation method of energy storage power stations, the cost is settled according to the output energy of the grid, and the income is settled according to the output energy of the battery. Therefore, energy efficiency has become one of the important reasons restricting the cost recovery of energy storage power stations.
[0004] Normally, the improvement of RTE is mainly achieved by regulating the battery control management system to operate in the appropriate SOC range (State of Charge) and keeping the battery operating at close to room temperature through the temperature control system. The above methods can basically ensure that the battery energy efficiency is about 80-85% (25℃, 1P, 2.0-3.65V), but it is difficult to further improve the energy efficiency. Summary of the invention
[0005] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the purpose of the present application is to propose a secondary battery and a preparation method thereof, and an electrical device, wherein the secondary battery has low impedance and high stability, and can achieve the purpose of adjusting the SEI structure according to demand to improve the cycle energy efficiency.
[0006] In one aspect of the present application, the present application provides a secondary battery. According to an embodiment of the present application, the secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte;
[0007] The electrolyte includes a free electrolyte and a non-free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet, and an electrolyte in the pores of the diaphragm;
[0008] The non-free electrolyte and the free electrolyte independently include at least one of a sulfonate compound and a sulfate compound;
[0009] Among them, the mass ratio of sulfonate compounds to sulfate compounds in the non-free electrolyte is T1, and the mass ratio of sulfonate compounds to sulfate compounds in the free electrolyte is T2, and T1 and T2 satisfy 0.1≤T1≤10, 0≤T2≤5.
[0010] The present application can optimize the charge and discharge performance of the battery, improve safety and stability, etc. by designing the localized distribution characteristics of the free electrolyte and the non-free electrolyte. When the mass ratio (T1) of sulfonate compounds to sulfate compounds in the non-free electrolyte satisfies 0.1≤T1≤10, it can be ensured that the sulfonate compounds and sulfate compounds in the non-free electrolyte support the formation of the required structure SEI in a suitable ratio. Combined with the mass ratio (T2) of sulfonate compounds to sulfate compounds in the free electrolyte satisfying 0≤T2≤5, the mass ratio of sulfonate compounds to sulfate compounds in the non-free electrolyte can be maintained at a suitable level, the SEI formed by chemical formation, and the structure after the SEI is broken and repaired during circulation or storage, that is, the inorganic components are always preferentially enriched in the inner layer, providing efficient ion conduction ability, and the organic components are always dispersed in the outer layer, exerting the repair ability, and the overall low impedance and high stability characteristics are presented, so as to achieve the purpose of regulating the SEI structure according to demand and thus improving the cycle energy efficiency.
[0011] In some embodiments of the present application, T1 and T2 satisfy T2<T1.
[0012] In some embodiments of the present application, the sulfonate compound includes at least one of a linear sulfonate compound and a cyclic sulfonate compound;
[0013] And / or, the sulfate ester compound includes at least one of a linear sulfate ester compound and a cyclic sulfate ester compound.
[0014] In some embodiments of the present application, the sulfonate compound includes at least one of trimethylsilyl trifluoromethanesulfonate, diethylene glycol dimethanesulfonate, 3,3-difluoropropyl methanesulfonate, 4-(trifluoromethyl)phenyl trifluoromethanesulfonate, 2-cyanophenyl trifluoromethanesulfonate, p-tolyl methanesulfonate, 4-nitrobenzyl methanesulfonate, propenyl-1,3-propane sultone, 1,4-propane sultone, 1,4-butane sultone, 2,4-butane sultone, tetrafluorosultone, 1,2,2-trifluoro-2-hydroxy-1-trifluoromethylethane sulfonic acid, 3-fluoro-1,3-propane sultone, and methylene disulfonate;
[0015] And / or, the sulfate ester compound includes at least one of trimethylene sulfate, 2-methyl-1,3-propanedisulfite, vinyl sulfate, 4-methyl vinyl sulfate, 4-ethyl vinyl sulfate, 4-propyl vinyl sulfate, 4-butyl vinyl sulfate, pentaerythritol bicyclic sulfate, and erythrose disulfate.
[0016] In some embodiments of the present application, the enrichment degree of sulfonate groups in the free electrolyte is F o , the F o Satisfy F o =0 or 1≤F o ≤2;
[0017] And / or, the enrichment degree of sulfate groups in the free electrolyte is F a , the F a Satisfy 1≤F a ≤1.8.
[0018] In some embodiments of the present application, the F o Satisfy 1.5≤F o ≤2;
[0019] and / or, the F a Satisfy 1≤F a ≤1.5.
[0020] In some embodiments of the present application, the positive electrode sheet has a first region and a second region on one side close to the diaphragm, the first region has a flat outer surface, and the second region is convex relative to the first region;
[0021] And / or, the negative electrode plate has a third region and a fourth region on one side close to the separator, the third region has a flat outer surface, and the fourth region is convex relative to the third region.
[0022] In some embodiments of the present application, the positive electrode sheet has the first region and the second region on one side close to the separator, and the design coefficient t of the positive electrode sheet is c =1+S ci / S c , the t c Satisfy 1.0≤t c ≤1.5;
[0023] Among them, S c S is the sum of the projected areas of the first region and the second region on the negative electrode sheet in the direction perpendicular to the diaphragm, ci is the surface area of the positive electrode sheet increased by the second region;
[0024] And / or, the negative electrode plate has a third region and a fourth region on one side close to the separator, and the design coefficient t of the negative electrode plate is a =1+S ai / S a , the t a Satisfy 1.0≤t a ≤1.5;
[0025] Among them, S a S is the sum of the projected areas of the third region and the fourth region on the positive electrode sheet in the direction perpendicular to the diaphragm in the negative electrode sheet, ai is the surface area of the negative electrode sheet increased by the fourth region;
[0026] And / or, the design coefficient t of the positive electrode plate c and the design coefficient t of the negative electrode plate a Satisfy 2.0<t c +t a ≤2.7.
[0027] In some embodiments of the present application, the enrichment degree F of the sulfonate groups in the free electrolyte is o , the enrichment degree F of sulfate groups in the free electrolyte a , the design coefficient t of the positive electrode plate c and the design coefficient t of the negative electrode plate a At least one of the following conditions is met:
[0028] F o / (t c +t a )=0;
[0029] 0.5≤F o / (t c +t a )≤1;
[0030] 0≤F a -0.7(t c +t a )+0.55≤0.8.
[0031] In a second aspect of the present application, the present application proposes a method for preparing the secondary battery according to the first aspect, comprising the following steps of injecting an electrolyte:
[0032] After the first injection is completed, the second injection is performed;
[0033] The electrolyte used in the first injection is a first electrolyte, and the electrolyte used in the second injection is a second electrolyte, and the first electrolyte and the second electrolyte independently include at least one of a sulfonate compound and a sulfate compound;
[0034] The mass proportion of the sulfonate compound in the first electrolyte is Mpo, and the mass proportion of the sulfate compound is Mpa, and the Mpa and Mpo satisfy 0<Mpa<Mpo≤3;
[0035] The mass proportion of sulfonate compounds in the second electrolyte is Mdo, and the mass proportion of sulfate compounds is Mda, and Mda and Mdo satisfy 0≤Mdo≤Mda≤3.
[0036] The secondary injection flexibly controls the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery by separating the electrolyte components required in the battery formation stage and the electrolyte components required in the circulation stage. In addition, limiting the amount of each compound added in the first electrolyte and the second electrolyte can ensure sufficient film formation without excessive reaction, and limiting the size of MPa and Mpo, as well as the size of Mda and Mdo can achieve the requirement of T2<T1.
[0037] In some embodiments of the present application, the mass ratio of the first electrolyte to the second electrolyte is (6:4) to (8:2);
[0038] And / or, the sum of the injection coefficients of the first electrolyte and the second electrolyte is 2.5 g / Ah to 5 g / Ah.
[0039] In a third aspect of the present application, the present application provides an electric device. According to an embodiment of the present application, the electric device includes the secondary battery described in the first aspect.
[0040] Therefore, the electrical equipment has all the advantages of the secondary battery, which will not be described in detail here.
[0041] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0043] Figure 1 One of the structural diagrams of the positive electrode sheet in the secondary battery provided by the present application is shown;
[0044] Figure 2One of the structural diagrams of the negative electrode sheet in the secondary battery provided by the present application is shown;
[0045] Figure 3 The second structural diagram of the negative electrode sheet in the secondary battery provided by the present application is shown;
[0046] Figure 4 The third structural diagram of the negative electrode sheet in the secondary battery provided by the present application is shown;
[0047] Figure 5 The fourth structural diagram of the negative electrode plate in the secondary battery provided by the present application is shown.
[0048] Reference numerals:
[0049] Positive electrode sheet 1, first region 10, second region 20, negative electrode sheet 2, third region 30, fourth region 40, width d1 of the fourth region, depth h1 of the fourth region. DETAILED DESCRIPTION
[0050] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.
[0051] In one aspect of the present application, the present application provides a secondary battery. According to an embodiment of the present application, the secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte;
[0052] The electrolyte includes a free electrolyte and a non-free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet, and an electrolyte in the pores of the diaphragm;
[0053] The non-free electrolyte and the free electrolyte independently include at least one of a sulfonate compound and a sulfate compound;
[0054] Among them, the mass ratio of sulfonate compounds to sulfate compounds in the non-free electrolyte is T1, and the mass ratio of sulfonate compounds to sulfate compounds in the free electrolyte is T2, and T1 and T2 satisfy 0.1≤T1≤10, 0≤T2≤5.
[0055] The applicant found that the inner inorganic component and the outer organic component are an ideal structure for enhancing the stability of SEI. As an additive that can effectively form SEI, the SO bond of sulfate compounds is broken after gaining electrons, and the -OSO2- group at the chain end combines with lithium ions to generate SEI products rich in ROSO2Li organic components. Sulfonate compounds also break the SO bond after gaining electrons, but the difference is that the -SO2- and -O- at the chain end combine with lithium ions to generate SEI products rich in Li2CO3 and Li2SO3 inorganic components; while the inorganic component in the layered SEI structure is more beneficial to the ion conduction ability of SEI, and the organic component is more beneficial to the self-repair ability of SEI. The combination of the two components forms an inner and outer layered distribution, which enables SEI to exert its low impedance and high stability properties and improve the cycle energy efficiency.
[0056] In addition, the present application designs the characteristics of localized distribution according to the requirements, that is, the electrolyte includes free electrolyte and non-free electrolyte. There is no absolute physical barrier between the non-free electrolyte and the free electrolyte in the battery cell. When the non-free electrolyte is insufficiently consumed, the free electrolyte is automatically absorbed as a supplement through the capillary action of the pole piece and the diaphragm. There are dynamic differences in the electrolyte components of the two regions during the cycle consumption process, so the component content of the battery during use is also dynamically changing. The present application stipulates that the mass ratio T1 of sulfonate compounds to sulfate compounds in the non-free electrolyte satisfies 0.1≤T1≤10, which can ensure that the sulfonate compounds and sulfate compounds in the non-free electrolyte support the formation of the required structure SEI in a suitable ratio. Specifically, T1 can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, etc. If T1 is too low, the sulfate compounds in the non-free electrolyte react first due to the concentration advantage, which is likely to cause more organic components in the inner layer of SEI and more inorganic components in the outer layer, which is manifested as large cell impedance, and energy efficiency deteriorates due to SEI instability and repeated generation of SEI during the cycle; if T1 is too high, the sulfonate compounds in the non-free electrolyte have a concentration advantage and continue to react, which is likely to cause both the inner and outer layers of SEI to contain a large amount of inorganic components and lack of organic components, which is manifested as SEI being easily destroyed, and also deteriorating energy efficiency.
[0057] At the same time, T2 satisfies 0≤T2≤5, and can maintain the mass ratio of sulfonate compounds to sulfate compounds in the non-free electrolyte at an appropriate level. The SEI formed by chemical formation and the structure after SEI rupture and repair during circulation or storage, the inorganic components are always preferentially enriched in the inner layer, providing efficient ion conductivity, and the organic components are always dispersed in the outer layer to exert the repair ability, showing the characteristics of low impedance and high stability as a whole, achieving the purpose of regulating the SEI structure according to demand to improve the cycle energy efficiency. Specifically, T2 can be 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc. When T2 is equal to 0, it means that the free electrolyte does not contain sulfonate compounds, but T1 is not 0, that is, it does not affect the participation of sulfonate compounds in the non-free electrolyte in film formation.
[0058] Specifically, the electrolyte of the present application includes a free electrolyte and a non-free electrolyte. The non-free electrolyte includes the electrolyte in the pores of the positive electrode sheet, the electrolyte in the pores of the negative electrode sheet and the electrolyte in the pores of the diaphragm, and the rest is the free electrolyte.
[0059] According to the embodiments of the present application, T1 and T2 satisfy T2<T1, thereby further ensuring that the sulfonate compounds and sulfate compounds in the non-free electrolyte support the formation of the required structure SEI in an appropriate ratio. If T2 is too high, exceeding T1, due to the characteristics of local electrolyte transfer, T1 is likely to rise rapidly, SEI is easily destroyed, and energy efficiency is deteriorated.
[0060] According to an embodiment of the present application, the non-free-state electrolyte and the free-state electrolyte independently include at least one of sulfonate compounds and sulfate compounds, that is, the non-free-state electrolyte may include at least one of sulfonate compounds and sulfate compounds, and the free-state electrolyte may include at least one of sulfonate compounds and sulfate compounds, and the types of sulfonate compounds in the non-free-state electrolyte and the free-state electrolyte may be the same or different, and the types of sulfate compounds may be the same or different.
[0061] According to the embodiments of the present application, the types of sulfonate compounds are not particularly limited, and those skilled in the art can select them according to actual needs. As some specific examples, the sulfonate compounds can select linear sulfonate compounds, cyclic sulfonate compounds, etc., including but not limited to trimethylsilyl trifluoromethylsulfonate, diethylene glycol dimethanesulfonate, 3,3-difluoropropyl methanesulfonate, 4-(trifluoromethyl)phenyl trifluoromethanesulfonate, 2-cyanophenyl trifluoromethanesulfonate, p-tolyl methanesulfonate, 4-nitrobenzyl methanesulfonate, propenyl-1,3-propane sultone, 1,4-propane sultone, 1,4-butane sultone, 2,4-butane sultone, tetrafluorosultone, 1,2,2-trifluoro-2-hydroxy-1-trifluoromethylethane sulfonic acid, 3-fluoro-1,3-propane sultone, and methylene disulfonate.
[0062] According to the embodiments of the present application, the types of sulfate ester compounds are not particularly limited, and those skilled in the art can select them according to actual needs. As some specific examples, the sulfate ester compounds can be selected from linear sulfate ester compounds and cyclic sulfate ester compounds, including but not limited to trimethylene sulfate, 2-methyl-1,3-propanedisulfite, vinyl sulfate, 4-methyl vinyl sulfate, 4-ethyl vinyl sulfate, 4-propyl vinyl sulfate, 4-butyl vinyl sulfate, pentaerythritol bicyclic sulfate, and erythrose disulfate.
[0063] According to an embodiment of the present application, the enrichment degree of sulfonate groups in the free electrolyte is F o , the F o Satisfy F o =0 or 1≤F o ≤2;
[0064] And / or, the enrichment degree of sulfate groups in the free electrolyte is F a , the F a Satisfy 1≤F a ≤1.8. Sulfonate groups and sulfate groups are effective film-forming functional groups introduced by adding sulfonate compounds and sulfate compounds to the electrolyte. The applicant has found that functional group richness has a more accurate prediction of battery performance than compound content. For compounds with the same content, the higher the functional group richness, the higher the content of groups participating in the reaction film formation, and the more significant the effect. By introducing the richness of sulfonate groups F o and sulfate group enrichment F a It can improve the battery cycle performance, which is more scientific than the conventional empirical addition and testing method. As some specific examples, F o It can be 0, 1, 1.5, 2, etc., preferably 1.5≤F o ≤2; F aIt can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, etc., preferably satisfying 1≤F a ≤1.5.
[0065] Specifically, the sulfonate group enrichment F o Sulfonate unit The ratio of the molar number of to the total molar number of compounds containing sulfonate groups, i.e. Where m on represents the mass content (g) of the nth compound containing a sulfonate group, M on represents the molar molecular weight (g / mol) of the nth compound containing a sulfonate group, x on represents the number of sulfonate units in the nth compound containing sulfonate groups, n is a natural number, when n = 0, F o =0.
[0066] Specifically, sulfate ester richness refers to the sulfate ester unit The ratio of the molar number of to the total molar number of compounds containing sulfate groups, i.e. Where m an represents the mass content (g) of the nth compound containing sulfate ester group, M an represents the molar molecular weight (g / mol) of the nth compound containing sulfate ester group, x an represents the number of sulfonate units in the nth compound containing sulfate groups, n is a natural number, when n = 0, F a =0.
[0067] According to the embodiments of the present application, referring to Figure 1-2 The positive electrode plate 1 has a first region 10 and a second region 20, the first region 10 has a flat outer surface, and the second region 20 is convex relative to the first region 10;
[0068] And / or, the negative electrode plate 2 has a third region 30 and a fourth region 40 on one side close to the separator, the third region 30 has a flat outer surface, and the fourth region 40 is convex relative to the third region 30. This increases the winding accuracy of the wound structure battery cell and reserves a certain space for the expansion of the plate.
[0069] Specifically, the number of the first area, the second area, the third area and the fourth area is not particularly limited, and those skilled in the art may adjust the number according to actual conditions.
[0070] Specifically, the second region is convexly arranged relative to the first region, wherein the second region can be arranged toward the diaphragm or away from the diaphragm, that is, a convex or concave structure. The shape of the second region is not particularly limited, and includes but is not limited to a sphere, a cylinder, a cube, a cone, etc. The width and depth of the second region are not particularly limited, wherein the depth is preferably 0.1-0.3 times the designed thickness of the electrode to avoid breaking the pole piece. The distribution of the second region on the pole piece is also not particularly limited, and is preferably regularly distributed, such as equidistantly distributed.
[0071] Specifically, the fourth region is convex relative to the third region, wherein the fourth region can be disposed toward the diaphragm or away from the diaphragm, that is, a convex or concave structure. The shape of the fourth region is not particularly limited, including but not limited to a sphere, a cylinder, a cube, a cone, etc., see Figure 2-4 The width d1 and depth h1 of the fourth region are not particularly limited, and the depth h1 is preferably 0.1-0.3 times the designed thickness of the electrode to avoid breaking the electrode sheet. The distribution of the fourth region on the electrode sheet is not particularly limited, and is preferably regularly distributed, such as equidistantly distributed.
[0072] According to an embodiment of the present application, the positive electrode sheet has the first region and the second region on one side close to the diaphragm, and the design coefficient t of the positive electrode sheet is c =1+S ci / S c , the t c Satisfy 1.0≤t c ≤1.5;
[0073] Among them, S c S is the sum of the projected areas of the first region and the second region on the negative electrode sheet in the direction perpendicular to the diaphragm, ci is the surface area of the positive electrode sheet increased by the second region;
[0074] And / or, the negative electrode plate has a third region and a fourth region on one side close to the separator, and the design coefficient t of the negative electrode plate is a =1+S ai / S a , the t a Satisfy 1.0≤t a ≤1.5;
[0075] Among them, S a S is the sum of the projected areas of the third region and the fourth region on the positive electrode sheet in the direction perpendicular to the diaphragm in the negative electrode sheet, ai is the surface area of the negative electrode sheet increased by the fourth region.
[0076] The applicant found that after the second region and / or the fourth region are set on the pole piece, the contact area between the pole piece and the electrolyte increases, which to a certain extent aggravates the consumption of electrolyte and the growth of cell impedance, affecting energy efficiency and cycle performance. At the same time, the applicant also found that the increase in the pole piece surface area caused by the second region and the fourth region also affects the demand for additives in the free electrolyte. Therefore, the design coefficient is introduced to limit the change in the contact area caused by the second region and / or the fourth region to improve the aforementioned problems.
[0077] Specifically, when the positive electrode sheet has the first region and the second region on one side close to the separator, the design coefficient t is introduced. c =1+S ci / S c , limiting it to satisfy 1.0≤t c ≤1.5, for example, t c is 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, etc. Among them, S c S is the sum of the projected areas of the first region and the second region on the negative electrode sheet in the direction perpendicular to the diaphragm, that is, the part of the positive electrode sheet that directly faces the negative electrode sheet through the diaphragm is the area of the positive electrode sheet that participates in the charge and discharge reaction. ci is the increase in the pole piece surface area caused by the second region.
[0078] Specifically, when the negative electrode sheet has a third region and a fourth region on the side close to the separator, the design coefficient t is introduced. a =1+S ai / S a , limiting it to satisfy 1.0≤t a ≤1.5, for example, t a is 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, etc. Among them, S a S is the sum of the projection areas of the third region and the fourth region on the positive electrode sheet in the direction perpendicular to the diaphragm, that is, the part of the negative electrode sheet that directly faces the positive electrode sheet through the diaphragm is the area of the negative electrode sheet that participates in the charge and discharge reaction. ai is the increase in the pole piece surface area caused by the fourth region.
[0079] About S ci , S c , S ai , S a The calculation method of the negative electrode is as follows: Figure 2-5 .in Figure 5 The negative electrode plate 2 has no fourth region, that is, no protrusions and depressions, then the S of the negative electrode plate aThat is, the projection area of the third region 30 on the positive electrode sheet in the direction perpendicular to the diaphragm, S ai is 0. Figure 2 The middle negative electrode sheet 2 has a third region 30 and a fourth region 40, and the fourth region 40 is a cube. a S is the sum of the projection areas of the third region 30 and the fourth region 40 on the positive electrode sheet in the direction perpendicular to the diaphragm, ai Then it is the sum of the areas of the five squares with a side length of d1 minus the projection area of the fourth region 40 on the positive electrode sheet (perpendicular to the diaphragm direction), and the calculation formula is:
[0080] S ai =5d1 2 -d1 2 =4d1 2 .
[0081] This formula corresponds to the case where only one fourth region is set on the negative electrode plate. If multiple fourth regions are set on the negative electrode plate, the increase in the surface area of the plate caused by each fourth region needs to be added together, and the same applies to the following.
[0082] Similarly, Figure 3 The fourth region 40 of the middle negative electrode plate 2 is hemispherical, and d1 corresponds to the diameter of the hemispherical shape. a S is the sum of the projection areas of the third region 30 and the fourth region 40 on the positive electrode sheet in the direction perpendicular to the diaphragm, ai The surface area of the hemisphere minus the projection area of the hemisphere on the positive electrode (perpendicular to the diaphragm) is calculated as follows:
[0083] S ai =2π(d1 / 2) 2 -π(d1 / 2) 2 =π(d1 / 2) 2 .
[0084] Figure 4 The fourth region 40 of the middle negative electrode sheet 2 is set to be conical, in which case d1 corresponds to the diameter of the bottom circle of the cone, and h1 corresponds to the height of the cone. a S is the projection area of the third region 30 and the fourth region 40 on the positive electrode sheet in the direction perpendicular to the diaphragm, ai Then it is the lateral area of the cone minus the projection area of the cone on the positive electrode (perpendicular to the diaphragm direction), and the calculation formula is
[0085]
[0086] Specifically, the second region and the fourth region can be prepared by conventional methods, such as embossing process, that is, processing the pole piece by a roller press. The shape, width, depth and other parameters of the second region and the fourth region can also be adjusted by adjusting the parameters of the roller press equipment.
[0087] According to an embodiment of the present application, the design coefficient t c and the design coefficient t of the negative electrode plate a Further satisfying 2.0<t c +t a ≤2.7. This can significantly suppress electrolyte consumption and avoid impedance surge or electrode bulging caused by the structural design on the electrode. As some specific examples, t c +t a It can be 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, etc.
[0088] According to an embodiment of the present application, the enrichment degree F of the sulfonate groups in the free electrolyte is o , the enrichment degree F of sulfate groups in the free electrolyte a , the design coefficient t of the positive electrode sheet c and the design coefficient t of the negative electrode plate a At least one of the following conditions is met:
[0089] F o / (t c +t a )=0;
[0090] 0.5≤F o / (t c +t a )≤1;
[0091] 0≤F a -0.7(t c +t a )+0.55≤0.8.
[0092] The applicant found that if there are too many sulfonate groups in the free electrolyte, SEI cannot be repaired in time, and the protrusions or depressions are more likely to cause continuous electrolyte loss due to weak interfaces. If there are too few sulfonate groups in the free electrolyte, lithium ions cannot be effectively transmitted, and the protrusions or depressions are more likely to aggravate lithium precipitation due to weak interfaces. Therefore, F is limited to o With t c +t a The relationship between F and sulfonate groups can ensure the number of sulfonate groups in the free electrolyte, thereby improving the energy efficiency of the battery. o / (t c +t a ) can satisfy Fo / (t c +t a )=0, or 0.5≤F o / (t c +t a )≤1, as some specific examples, F o / (t c +t a ) can be 0, 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc.
[0093] In addition, the applicant also found that if there are too many sulfate groups in the free electrolyte, lithium ions cannot be effectively transmitted, and lithium is more likely to be deposited at the protrusions or depressions. If there are too few sulfate groups in the free electrolyte, SEI cannot be repaired in time, and byproducts are more likely to accumulate and produce scars at the protrusions or depressions. Lithium deposition and byproduct scars caused by unreasonable additives and protrusion or depression design will directly deteriorate battery energy efficiency. Therefore, 0≤F can also be limited a -0.7(t c +t a )+0.55≤0.8, which can not only significantly inhibit the consumption of electrolyte, but also inhibit the accumulation of by-products, and will not cause a sharp increase in battery cell impedance or electrode swelling.
[0094] According to some specific embodiments of the present application, during the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte conducts ions between the positive electrode sheet and the negative electrode sheet. The isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet to prevent the positive and negative electrodes from short-circuiting while allowing ions to pass through.
[0095] According to some specific embodiments of the present application, the secondary battery is a lithium-ion secondary battery.
[0096] According to some specific embodiments of the present application, the positive electrode plate includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes a positive active material and the above-mentioned lithium supplement, wherein the positive active material is preferably a lithium iron phosphate material.
[0097] According to some specific embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0098] According to some specific embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0099] According to some specific embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0100] According to some specific embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the positive electrode sheet, such as the positive electrode active material, the lithium supplement agent, the conductive agent, and the binder are dispersed in a solvent (such as N-methylpyrrolidone, NMP) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0101] According to some specific embodiments of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material.
[0102] According to some specific embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one side of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0103] According to some specific embodiments of the present application, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.
[0104] According to some specific embodiments of the present application, the negative electrode active material layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0105] According to some specific embodiments of the present application, the negative electrode active material layer may further optionally include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0106] According to some specific embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0107] According to some specific embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0108] According to some specific embodiments of the present application, the present application has no particular restrictions on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. In some embodiments of the present application, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.
[0109] According to some specific embodiments of the present application, the positive electrode sheet, the negative electrode sheet and the isolation film can be made into an electrode assembly through a winding process or a lamination process.
[0110] According to some specific embodiments of the present application, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0111] According to some specific embodiments of the present application, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, polybutylene succinate, etc. can be listed.
[0112] In a second aspect of the present application, the present application proposes a method for preparing the secondary battery described in the first aspect. According to an embodiment of the present application, the preparation method comprises the following steps of injecting an electrolyte:
[0113] After the first injection is completed, the second injection is performed;
[0114] The electrolyte used in the first injection is a first electrolyte, and the electrolyte used in the second injection is a second electrolyte, and the first electrolyte and the second electrolyte independently include at least one of a sulfonate compound and a sulfate compound;
[0115] The mass proportion of the sulfonate compound in the first electrolyte is Mpo, and the mass proportion of the sulfate compound is Mpa, and the Mpa and Mpo satisfy 0<Mpa<Mpo≤3;
[0116] The mass proportion of sulfonate compounds in the second electrolyte is Mdo, and the mass proportion of sulfate compounds is Mda, and Mda and Mdo satisfy 0≤Mdo≤Mda≤3.
[0117] The present application adopts the method of secondary liquid injection to prepare the aforementioned secondary battery, and flexibly controls the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery by separating the electrolyte components required for the battery formation stage and the electrolyte components required for the circulation stage. The applicant found that the local distribution characteristics of the electrolyte in the initial state determine the local distribution characteristics of the electrolyte in the subsequent working state: under the premise that the total amount of electrolyte is sufficient and the transmission is unobstructed, the local distribution ratio of additives in the electrolyte in the initial state can qualitatively determine the local distribution ratio of additives in the electrolyte in the subsequent working state. Therefore, limiting the amount of sulfonate compounds and sulfate compounds added in the secondary liquid injection can achieve localized distribution of the electrolyte. Specifically, the product of sulfate compounds is rich in ROSO2Li organic components, which is more beneficial to the self-repair ability of SEI, and the product of sulfonate compounds is rich in Li2CO3 and Li2SO3 inorganic components, which is more beneficial to the ion conductivity of SEI. By limiting the Mpo in the first electrolyte to be no less than Mpa and the Mda in the second electrolyte to be no less than Mdo, T2<T1 can be achieved. pa 、M po 、M do 、M da The upper limit value is 3, which can achieve sufficient film formation without excessive reaction.
[0118] According to an embodiment of the present application, the first electrolyte and the second electrolyte independently include at least one of a sulfonate compound and a sulfate compound, that is, the first electrolyte may include at least one of a sulfonate compound and a sulfate compound, and the second electrolyte may include at least one of a sulfonate compound and a sulfate compound, and the types of sulfonate compounds in the first electrolyte and the second electrolyte may be the same or different, and the types of sulfate compounds may be the same or different.
[0119] According to an embodiment of the present application, the mass ratio of the first electrolyte to the second electrolyte is (6:4) to (8:2). As some specific examples, the mass ratio of the first electrolyte to the second electrolyte may be 6:4, 7:3, 8:2, etc. This can improve the battery cycle performance. When the mass ratio of the first electrolyte to the second electrolyte is lower than 6:4, the amount of liquid injection during the first injection (first injection) is insufficient for full infiltration, and the SEI protective layer obtained by chemical formation is uneven. After the second injection (second injection), there is no area where SEI is formed and the electrolyte is electronically conductive, resulting in the decomposition and accumulation of electrolyte byproducts; if the mass ratio of the first electrolyte to the second electrolyte is too high, that is, greater than 8:2, the proportion of the second injection is low, and the free electrolyte component mainly comes from the electrolyte component that has not been consumed in the first injection, which is basically the same as the non-free electrolyte component. At this ratio, there is basically no difference between the second injection and the traditional first injection, and it is difficult to achieve the design of a localized electrolyte.
[0120] According to an embodiment of the present application, the sum of the injection coefficients of the first electrolyte and the second electrolyte is 2.5g / Ah to 5g / Ah. As some specific examples, the sum of the injection coefficients of the first electrolyte and the second electrolyte may be 2.5g / Ah, 3g / Ah, 3.5g / Ah, 4g / Ah, 4.5g / Ah, 5g / Ah, etc., preferably 3.5g / Ah to 4.5g / Ah. Specifically, the injection coefficient (injection amount / cell capacity) represents the electrolyte demand. For lithium-ion batteries for energy storage, a higher injection coefficient can maintain a long cycle life. The present application limits the sum of the injection coefficients of the two injections within a suitable range, which can achieve sufficient wetting of the diaphragm and the pole piece, and avoid swelling due to excessive electrolyte or accumulation at the bottom of the battery to cause local lithium precipitation.
[0121] According to a specific embodiment of the present application, the preparation method can be carried out through the following steps: first liquid injection, static formation, second liquid injection, high temperature aging, and capacity division to obtain the secondary battery. Among them, the static aging and formation process are not particularly limited, and it can be ensured that the infiltration is sufficient and the formation film is uniform. The battery can be fully charged and disassembled before the second liquid injection and before capacity division. Visible electrolyte is distributed at all positions of the positive and negative electrodes and the diaphragm in the battery, and there are no abnormal spots or dark marks on the negative electrode, which meets the requirements. The full charging process can be charged to 3.65V at a constant current of 0.2C.
[0122] In a third aspect of the present application, the present application provides an electric device. According to an embodiment of the present application, the electric device includes the secondary battery described in the first aspect.
[0123] According to some specific embodiments of the present application, the secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, and the like. Among them, the electric toy can include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, an electric airplane toy, and the like, and the spacecraft can include an airplane, a rocket, a space shuttle, a spacecraft, and the like.
[0124] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0125] The batteries of each embodiment and comparative example were prepared according to the following method:
[0126] (1) Preparation of positive electrode sheet:
[0127] The positive electrode active material lithium iron phosphate (LiFePO4), conductive carbon black (SP), and adhesive polyvinylidene fluoride (PVDF) were dispersed in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 97:2.5:0.5 and mixed evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on the positive electrode current collector aluminum foil. The coating weight per unit area of the positive electrode slurry was 33 mg / cm 2 After embossing, drying, cold pressing, slitting and cutting, the positive electrode sheet is obtained;
[0128] (2) Preparation of negative electrode sheet:
[0129] The negative electrode active material artificial graphite, conductive carbon black (SP), thickener (CMC) and binder (SBR) were dispersed in deionized water at a mass ratio of 96.5:0.5:1:2 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil. The coating weight per unit area of the negative electrode slurry was 16 mg / cm 2 After drying, cold pressing, embossing, slitting and cutting, the negative electrode sheet is obtained;
[0130] (3) Preparation of electrolyte:
[0131] In an argon atmosphere glove box with a moisture and oxygen content of ≤0.1ppm, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate were mixed in a mass ratio of 1:1:1, and 1M lithium hexafluorophosphate, 3% vinylene carbonate, and the additives shown in the table were added according to the design in Table 1-3, and stirred until completely dissolved;
[0132] (4) Preparation of diaphragm:
[0133] A 16 μm polyethylene film was used as the separator;
[0134] (5) Battery assembly:
[0135] The prepared positive electrode sheet, separator and negative electrode sheet are stacked in order so that the separator is in the middle of the positive and negative electrodes to separate the positive and negative electrode sheets, and then wound into a bare battery cell. After welding the pole ears, the battery cell is assembled into the outer packaging, vacuum dried after hot pressing, and then the liquid injection process is carried out.
[0136] In one of the single injection groups, such as Comparative Examples 1-1 and 1-6, the following preparation method is adopted: injecting electrolyte, packaging the battery cell, standing, forming, high-temperature standing, capacity testing, etc., and finally preparing a soft-pack lithium-ion battery with a capacity of 3.2Ah.
[0137] The secondary injection group adopts the following preparation method: the electrolyte is injected for the first time, the battery cell is packaged, left to stand, and formed; the electrolyte is injected for the second time, the battery cell is left to stand at high temperature, and the capacity is tested, etc., and finally a soft-pack lithium-ion battery with a capacity of 3.2Ah is prepared.
[0138] The formation of the first injection and the second injection adopts the following steps:
[0139] (1) The battery cell was placed in a 45°C formation cabinet for 10 min and charged at 0.1C for 7 min to 1.17% SOC;
[0140] (2) Let stand for 3 min and charge at 0.2C rate to 30% SOC.
[0141] Different a ,t c The positive and negative electrode sheets are not limited to being obtained by adjusting the parameters of the roller press equipment, but may also include designing the embossing shape, embossing single point distribution, embossing local distribution, etc., or other subsequent processing methods of the bare battery cell, such as cold pressing parameter adjustment, etc.
[0142] In Table 1, the positive and negative electrode sheets are not embossed; the injection coefficient is 4.0g / Ah; the injection ratio of the first injection and the second injection is 7:3; the standing condition after the first injection is 45±5℃ for 24 hours, the formation temperature is 45℃, and the standing condition after the second injection (high temperature aging) is 45±5℃ for 24 hours.
[0143] In Table 2, the design parameters for embossing the positive and negative electrode sheets are specifically listed; the injection coefficient, the ratio of the first injection and the second injection, the temperature and time parameters in the second injection are consistent with those in Table 1. Among them, the first and second injections of electrolyte in Example 2-1 are consistent with those in Example 1-1, the first and second injections of electrolyte in Example 2-2 are consistent with those in Example 1-11, and the first and second injections of electrolyte in Example 2-3 are consistent with those in Example 1-28. The first and second injections of electrolyte in Examples 2-12 to 2-15 are consistent, and the first and second injections of electrolyte in Examples 2-16 to 2-17 are consistent with those in Comparative Example 2-1. The specific enumeration is shown in Table 2.
[0144] In Table 3, the injection coefficient and the injection ratio of the first injection and the second injection are specifically listed; the temperature and time conditions in the second injection are consistent with those in Table 1 and Table 2. Among them, the first injection and the second injection electrolyte composition and material ratio in Examples 3-1 to 3-10 remain unchanged, which is consistent with Examples 1-28 and 2-3.
[0145] (1)S ci , S c , S ai , S a calculate:
[0146] Where S c is the sum of the projected areas of the first region and the second region on the negative electrode sheet in the direction perpendicular to the diaphragm in the positive electrode sheet;
[0147] S a is the sum of the projected areas of the third region and the fourth region on the positive electrode sheet in the direction perpendicular to the diaphragm in the negative electrode sheet;
[0148] S ci The sum of the electrode surface area increments caused by each second region, wherein the electrode surface area increment caused by each second region is calculated as follows: the surface area of the second region minus the projection area of the second region on the negative electrode electrode (perpendicular to the diaphragm direction);
[0149] S ai It is the sum of the electrode surface area increments caused by each fourth region, wherein the electrode surface area increment caused by each fourth region is calculated as follows: the surface area of the fourth region minus the projection area of the fourth region on the negative electrode electrode (perpendicular to the diaphragm direction).
[0150] (2) Test of free electrolyte composition:
[0151] Discharge the battery with outer packaging with a current of 0.05C to 0% SOC (2.5V), cut a notch of about 0.5cm on the right side of the battery facing the positive column, and cut the same notch on the right side facing the negative column, ensuring that the two notches are on the diagonal line, and pour the free electrolyte into the fluoride bottle from the small opening on the side of the positive column until intermittent dripping flows down and count for 30s.
[0152] Gas chromatography-mass spectrometry (GC-MS) was used to test the relative mass content of additives in the collected electrolyte.
[0153] (3) Non-free (pore) electrolyte test:
[0154] Remove the outer packaging, take out a single bare cell, quickly peel off the electrode, put it into an aluminum-plastic bag, add enough acetonitrile solvent to completely immerse the electrode, seal the aluminum-plastic bag containing acetonitrile solvent and electrode, and let it stand at 35±10℃ for 3 days.
[0155] The relative mass content of additives in the collected electrolyte was determined using GC-MS.
[0156] (4) Calculation of enrichment of additive design parameters:
[0157] Sulfonate group enrichment
[0158] Where m on represents the mass content (g) of the nth compound containing a sulfonate group, M on represents the molar molecular weight (g / mol) of the nth compound containing a sulfonate group, x on represents the number of sulfonate units in the nth compound containing sulfonate groups, n is a natural number, when n = 0, F o =0.
[0159] Sulfate group richness
[0160] Where m an represents the mass content (g) of the nth compound containing sulfate ester group, M an represents the molar molecular weight (g / mol) of the nth compound containing a sulfate group, x an represents the number of sulfonate units in the nth compound containing sulfate groups, n is a natural number, when n = 0, F a =0.
[0161] (5) Energy efficiency performance test:
[0162] Charge to 3.65V at 0.5P constant power at 25℃, then discharge to 2.5V at 0.5P constant power. The capacity of the Xth charge and discharge cycle is recorded as CCx, DCx, and the energy of the Xth charge and discharge cycle is recorded as CEx, DEx, until X=500.
[0163] The battery RTE is evaluated by the post-cycle energy efficiency η, η = DE 500 / CE 500 .
[0164] Table 1
[0165]
[0166]
[0167] Table 1
[0168]
[0169]
[0170]
[0171] Here, “ / ” indicates non-existence.
[0172] Table 1 tests the relationship between the design parameters of free electrolyte and non-free electrolyte and the cycle energy efficiency. Comparative Examples 1-7 use the traditional one-time injection process, and use sulfonate (1,3-propane sultone) and sulfate (vinyl sulfate) additives at the same time; Comparative Examples 1-8 use the two-time injection process, and use sulfonate and sulfate additives only in one injection; Comparative Examples 1-9 use the two-time injection process, and use sulfonate and sulfate additives only in two injections; Comparative Examples 1-10 use the two-time injection process, and use sulfate additives only in one injection, and use sulfonate additives only in two injections; Comparative Examples 1-11 use the two-time injection process, and use sulfonate additives only in one injection, and use sulfate additives only in two injections. Because the two-time injection process adopts an injection ratio of 7:3, the corresponding contents of sulfonate (1,3-propane sultone) and sulfate (vinyl sulfate) additives in Comparative Examples 1-7 to Comparative Examples 1-11 are adjusted to keep the actual amount of additives consistent.
[0173] The test results show that the design parameters T1 and T2 of comparative examples 1-7 to 1-11 are beyond the scope specified in the present application, and the characteristics of localized distribution of sulfate and sulfonate additives in the battery cannot be achieved. The cycle energy efficiency performance is poor, basically below 87%.
[0174] Comparative Examples 1-12 use the traditional one-time liquid injection process and use sulfonate and sulfate additives at the same time, but only change the compound types of sulfate and sulfonate additives. From the test results, it can be seen that only by optimizing the compound types of additives, the design parameters T1 and T2 still exceed the specified range of this application, and the cycle energy efficiency is improved, but still cannot exceed 90%.
[0175] Examples 1-1 to 1-33, and Comparative Example 1-6 use a secondary injection process, and it is not limited whether the sulfonate and sulfate additives are the same in the first injection and the second injection. From the experimental values of the design parameters T1, T2, and cycle energy efficiency, the localized distribution of sulfonate compounds and sulfate compounds in the electrolyte can be analyzed, and their direct impact on battery performance.
[0176] For Example 1-1 to Example 1-9, and Comparative Example 1-1 to Comparative Example 1-4, the addition amount Mdo and Mda of sulfonate (1,3-propane sultone) and sulfate (vinyl sulfate) additives in two injections of electrolyte are fixed, and the addition amount Mpo and MPa of sulfonate (1,3-propane sultone) and sulfate (vinyl sulfate) additives in one injection of electrolyte are adjusted, and different T1 and T2 design parameters are obtained. It can be seen that compared with the comparative example, when T2 < T1, the battery cycle energy efficiency can be effectively improved. This is because the mass ratio of sulfonate compounds / sulfate compounds in the non-free electrolyte is at a suitable level. Regardless of the SEI formed by chemical formation and the structure after SEI rupture and repair during circulation or storage, the inorganic components are always preferentially enriched in the inner layer, providing efficient ion conductivity, and the organic components are always dispersed in the outer layer, exerting the repair ability, and the overall low impedance and high stability are shown, thereby improving the cycle energy efficiency. However, the distribution range of T1 and T2 needs to be controlled. If T1 is too low, such as when Comparative Examples 1-1 and 1-2 are lower than 0.1, the sulfate compounds in the non-free electrolyte react first due to the concentration advantage competition, which easily causes more organic components in the inner layer of SEI and more inorganic components in the outer layer, which is manifested as large cell impedance, and low energy efficiency due to the instability of SEI and repeated generation of SEI during the cycle; if T1 is too high, such as when Comparative Examples 1-4 are higher than 10, the sulfonate compounds in the non-free electrolyte have a concentration advantage and continue to react, which easily causes the inner and outer layers of SEI to contain a large amount of inorganic components and lack organic components, which is manifested as SEI being easily destroyed, and also causing energy efficiency to deteriorate. Similarly, in Comparative Examples 1-13, because MPa is 0 and MDA is 0, the ranges of T1 and T2 tend to infinity, and the sulfonate compounds have a concentration advantage and continue to react, which also causes energy efficiency to deteriorate. In addition, the cycle energy efficiency performance of Example 1-1 is the best, which can reach more than 94%.
[0177] For Examples 1-10 to 1-18 and Comparative Examples 1-5 to 1-6, the addition amounts Mpo and Mpa of sulfonate (1,3-propane sultone) and sulfate (ethylene sulfate) additives in one portion of the electrolyte were fixed, and by adjusting the addition amounts Mdo and Mda of sulfonate (1,3-propane sultone) and sulfate (ethylene sulfate) additives in the second portion of the electrolyte, different T1 and T2 design parameters were obtained. Similarly, it can be seen that when T2 < T1, the battery cycle energy efficiency can be effectively improved, but the distribution ranges of T1 and T2 need to be controlled. If T2 is too high, such as higher than 5 in Comparative Examples 1-5 to 1-6, the sulfonate group compounds in the free electrolyte have a concentration advantage. After supplementing to the non-free portion, the continuous reaction is likely to cause a large amount of inorganic components in both the inner and outer layers of the SEI and lack organic components, manifested as the SEI being easily damaged, and the energy efficiency also deteriorates.
[0178] For Examples 1-19 to 1-33, the addition amounts Mpo, Mpa, Mdo, and Mda of sulfonate and sulfate additives in one portion and the second portion of the electrolyte were fixed, the compound types of sulfonate and sulfate additives were adjusted, and a variety of compound additives were designed and mixed for verification. It is not difficult to see from the results that compared with Example 1-1, changing the compound types of sulfonate and sulfate additives or using them in combination has a slight impact on the design parameters T1, T2 and the cycle energy efficiency. Among them, Examples 1-26, 1-28, 1-31, and 1-32 can further optimize the cycle energy efficiency. Changing the compound types of sulfonate and sulfate additives or using them in combination does not affect the relationship of T2 < T1, indicating that the solution of this application is universal for the effects of such substances.
[0179] Table 2
[0180]
[0181]
[0182] Continued Table 2
[0183]
[0184]
[0185] Among them, " / " indicates non-existence.
[0186] Table 2 tests the relationship between the design parameters of additives in the free electrolyte and the embossing design coefficient in terms of their impact on the cycle energy efficiency. In Table 2, Example 1-1, Example 1-11, Example 1-28, and Comparative Example 2-1 were not embossed, so the design parameters tc=ta=1.00, tc+ta=2.00. By comparing Example 1-1 with Example 2-1, Example 1-11 with Example 2-2, Example 1-28 with Example 2-3, and Comparative Example 2-1 with Example 2-17, it can be found that the introduction of electrode embossing in the original electrolyte design system does not necessarily improve the cycle energy efficiency. For example, after using embossed electrodes in Example 2-1 and Example 2-17, the energy efficiency is slightly reduced, and the energy efficiency of Example 2-3 does not change significantly after using embossed electrodes. By analyzing the relationship between Fo, Fa and tc+ta, it can be seen that exceeding the required range of design parameters will cause a certain degree of performance reduction. This is because the degree of increase in the electrode area caused by embossing is different, and the demand for sulfonate groups and sulfate groups in the free electrolyte is also different. If there are too many sulfonate groups in the free electrolyte, SEI cannot be repaired in time, and the embossing is more likely to cause continuous electrolyte loss due to weak interfaces. If there are too few sulfonate groups in the free electrolyte, lithium ions cannot be effectively transmitted. The embossing is more likely to aggravate lithium precipitation due to weak interfaces. On the contrary, if there are too many sulfate groups in the free electrolyte, lithium ions cannot be effectively transmitted, and lithium precipitation is more likely to occur at the embossing. If there are too few sulfate groups in the free electrolyte, SEI cannot be repaired in time, and by-products are more likely to accumulate and produce scars at the embossing. Lithium precipitation and by-product scars caused by unreasonable additives and embossing design will directly deteriorate battery energy efficiency.
[0187] Embodiments 2-3 to 2-17 obtain different Fo and Fa by adjusting the types and contents of sulfonate and sulfate additives in the free electrolyte, and further obtain the change values of the design parameters Fo / (tc+ta) and Fa-0.7(tc+ta)+0.55 by adjusting the embossing design coefficients tc and ta. It can be found from the test results that when 1.5≤Fo≤2, 1≤Fa≤1.5, and 2.0<tc+ta≤2.7, a higher cycle energy efficiency can be achieved, especially in Embodiments 2-8 and 2-15, the energy efficiency can exceed 95%. The range of values of Fo and Fa shows that sulfonate-rich compounds and oligosulfate-rich compounds tend to be used in the free electrolyte, which also means that when the additives are mixed, the free electrolyte needs to contain polysulfonate-rich compounds and monosulfate-rich compounds. The value range of tc+ta shows that the degree of embossing should not be excessive. Even if the electrode has good pressure resistance and is not broken, excessive increase in the area of contact reaction with the electrolyte will cause serious deterioration of battery performance.
[0188] Table 3
[0189]
[0190]
[0191] Table 3 tests the effects of the secondary injection electrolyte injection coefficient and injection mass ratio on the additive enrichment in the free electrolyte, design parameters, and the cycle energy efficiency.
[0192] Example 3-1 The injection mass ratio is too low, the diaphragm and the electrode cannot be fully infiltrated, resulting in a lack of film protection in the electrode that has not entered the electrolyte during the formation stage. o / (t c +t a ) is also less than 0.5, which exceeds the design range requirements and deteriorates the energy efficiency. Example 3-6 The electrolyte volume is too much and the redundant electrolyte will accumulate at the bottom of the battery to cause lithium precipitation. At this time, F o / (t c +t a ) is also less than 0.5, which exceeds the limited range. Therefore, the injection coefficient of the sum of the first injection electrolyte and the second injection electrolyte is limited to 2.5g / Ah~5g / Ah. From the perspective of energy efficiency, 3.5g / Ah~4.5g / Ah is preferred.
[0193] In Example 3-7, since the ratio of the amount of liquid in the first and second injections is too low, that is, less than 6:4, the amount of liquid in the first injection is insufficient for full infiltration, and the SEI protective layer obtained by the formation is uneven. After the second injection, the area where SEI is not formed and the electrolyte are electronically conductive, resulting in the decomposition and accumulation of electrolyte byproducts; in Example 3-10, the ratio of the amount of liquid in the first and second injections is too high, that is, greater than 8:2, then the proportion of the second injection is low, and the free electrolyte components mainly come from the electrolyte components that are not consumed in the first injection, and are basically the same as the non-free electrolyte components. Under such a ratio, there is basically no difference between the second injection and the traditional first injection, and it is difficult to realize the design of the localized electrolyte. Therefore, the mass ratio of the electrolyte in the first injection and the second injection is limited to 6:4 to 8:2. In Example 3-11, after finely adjusting the injection coefficient and the mass ratio of the second injection on the basis of Example 2-15, the cycle capacity retention rate and energy efficiency are also further improved, up to 96.5%.
[0194] By comparing Example 2-3 with Example 3-3 and Example 3-4, and comparing Example 2-15 with Example 3-11, it can be seen that within the appropriate range of injection coefficient and injection mass ratio, the influence of the distribution of additives in the free electrolyte is very small. Under the premise of meeting the design parameters, this solution can still be implemented.
[0195] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0196] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; The electrolyte includes a free electrolyte and a non-free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet, and an electrolyte in the pores of the diaphragm; The non-free electrolyte and the free electrolyte independently include at least one of a sulfonate compound and a sulfate compound; Among them, the mass ratio of sulfonate compounds to sulfate compounds in the non-free electrolyte is T1, and the mass ratio of sulfonate compounds to sulfate compounds in the free electrolyte is T2, and T1 and T2 satisfy 0.1≤T1≤10, 0≤T2≤5.
2. The secondary battery according to claim 1, characterized in that: The T1 and T2 satisfy T2<T1.
3. The secondary battery according to claim 1, characterized in that: The sulfonate compound includes at least one of a linear sulfonate compound and a cyclic sulfonate compound; And / or, the sulfate ester compound includes at least one of a linear sulfate ester compound and a cyclic sulfate ester compound.
4. The secondary battery according to claim 1, characterized in that: The sulfonate compound includes at least one of trimethylsilyl trifluoromethanesulfonate, diethylene glycol dimethanesulfonate, 3,3-difluoropropyl methanesulfonate, 4-(trifluoromethyl)phenyl trifluoromethanesulfonate, 2-cyanophenyl trifluoromethanesulfonate, p-tolyl methanesulfonate, 4-nitrobenzyl methanesulfonate, propenyl-1,3-propane sultone, 1,4-propane sultone, 1,4-butane sultone, 2,4-butane sultone, tetrafluorosultone, 1,2,2-trifluoro-2-hydroxy-1-trifluoromethylethane sulfonic acid, 3-fluoro-1,3-propane sultone, and methylene methanedisulfonate; And / or, the sulfate ester compound includes at least one of trimethylene sulfate, 2-methyl-1,3-propanedisulfite, vinyl sulfate, 4-methyl vinyl sulfate, 4-ethyl vinyl sulfate, 4-propyl vinyl sulfate, 4-butyl vinyl sulfate, pentaerythritol bicyclic sulfate, and erythrose disulfate.
5. The secondary battery according to claim 1, characterized in that: The enrichment degree of sulfonate groups in the free electrolyte is F o , the F o Satisfy F o =0 or 1≤F o ≤2; And / or, the enrichment degree of sulfate groups in the free electrolyte is F a , the F a Satisfy 1≤F a ≤1.
8.
6. The secondary battery according to claim 5, characterized in that: The F o Satisfy 1.5≤F o ≤2; and / or, the F a Satisfy 1≤F a ≤1.
5.
7. The secondary battery according to claim 5 or 6, characterized in that: The positive electrode sheet has a first region and a second region on one side close to the diaphragm, the first region has a flat outer surface, and the second region is convex relative to the first region; And / or, the negative electrode plate has a third region and a fourth region on one side close to the separator, the third region has a flat outer surface, and the fourth region is convex relative to the third region.
8. The secondary battery according to claim 7, characterized in that: The positive electrode sheet has the first region and the second region on one side close to the separator, and the design coefficient t of the positive electrode sheet is c =1+S ci / S c , the t c Satisfy 1.0≤t c ≤1.5; Among them, S c S is the sum of the projected areas of the first region and the second region on the negative electrode sheet in the direction perpendicular to the diaphragm, ci is the surface area of the positive electrode sheet increased by the second region; And / or, the negative electrode plate has a third region and a fourth region on one side close to the separator, and the design coefficient t of the negative electrode plate is a =1+S ai / S a , the t a Satisfy 1.0≤t a ≤1.5; Among them, S a S is the sum of the projected areas of the third region and the fourth region on the positive electrode sheet in the direction perpendicular to the diaphragm in the negative electrode sheet, ai is the surface area of the negative electrode sheet increased by the fourth region; And / or, the design coefficient t of the positive electrode plate c and the design coefficient t of the negative electrode plate a Satisfy 2.0<t c +t a ≤2.
7.
9. The secondary battery according to claim 8, characterized in that: The enrichment degree F of sulfonate groups in the free electrolyte o , the enrichment degree F of sulfate groups in the free electrolyte a , the design coefficient t of the positive electrode sheet c and the design coefficient t of the negative electrode plate a At least one of the following conditions is met: F o / (t c +t a )=0; 0.5≤F o / (t c +t a )≤1; 0≤F a -0.7(t c +t a )+0.55≤0.8。 10. A method for preparing a secondary battery according to any one of claims 1 to 9, characterized in that: The steps of injecting electrolyte include: After the first injection is completed, the second injection is performed; The electrolyte used in the first injection is a first electrolyte, and the electrolyte used in the second injection is a second electrolyte, and the first electrolyte and the second electrolyte independently include at least one of a sulfonate compound and a sulfate compound; The mass proportion of the sulfonate compound in the first electrolyte is Mpo, and the mass proportion of the sulfate compound is Mpa, and the Mpa and Mpo satisfy 0<Mpa<Mpo≤3; The mass proportion of sulfonate compounds in the second electrolyte is Mdo, and the mass proportion of sulfate compounds is Mda, and Mda and Mdo satisfy 0≤Mdo≤Mda≤3.
11. The preparation method according to claim 10, characterized in that: The mass ratio of the first electrolyte to the second electrolyte is (6:4) to (8:2); And / or, the sum of the injection coefficients of the first electrolyte and the second electrolyte is 2.5 g / Ah to 5 g / Ah.
12. An electrical device, characterized in that: The electrical device comprises the secondary battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electrolyte for lithium secondary battery, secondary battery, and electric device
CN117083745A
Electrolyte preparation method, battery, vehicle and storage medium
CN118156619A
Electrolyte for secondary liquid injection, secondary liquid injection method and battery
CN118712488A
Lithium ion secondary battery
JP2019160615A